Physicians’ perspectives on chiropractic treatment - Verhoef, Marja J (1996)
The objective of this study was to examine general practitioners’ opinions and behaviours concerning chiropractic. The study was a secondary analysis of the data collected in a cross-sectional survey of 400 general practitioners from Alberta and Ontario that assessed opinions and behaviours concerning several types of complementary medicine. The response rate was 52% Twenty-eight percent indicated they had considerable knowledge about chiropractic, overall 58% found chiropractic useful or very useful and 43% believed that chiropractic is efficacious for neck and back problems. Forty-four percent of the total sample stated they referred patients to chiropractors, primarily for back pain, musculoskeletal indications in general and chronic pain. Efforts need to be made to further improve the relationship between general practitioners and chiropractors and, thus, establish chiropractic as a viable treatment option.